Venous thromboembolism in Thai children - Nongnuch Sirachainan (2018)
□ This is a retrospective study of 24 pediatric venous thromboembolism (VTE) patients with or without pulmonary embolism, conducted in Bangkok, Thailand, between 1981 and 2005. The incidence rate of VTE in Thai children was 3.9/10,000 hospital admissions per year. The median age was 11.7 years. Seventy-five percent of the patients had at least one associated medical condition accounting for the VTE; the two most common conditions, however, were infection and malignancy. Pulmonary embolism occurred in 29% of patients. Observed outcomes of VTE in this series included death (13%), postphlebitic syndrome (13%), and recurrence (26%). Genetic risk factors were explored in 19 patients, and no factor V Leiden or prothrombin 20210 mutations were detected. Protein C deficiency was found in 4 patients. Copyright © Informa Healthcare.